An Experimental Study on The Effects of Milling Process Parameters Towards Product Surface Quality - AZHARI, MUHAMMAD SYAHIR; Hehsan, Haffidzudin (Progress in Engineering Application and Technology, 2023)
The surface finish was emphasized in the machining process because it refer to the quality of the product. Surface finish was referred to surface roughness. To obtain high quality of surface roughness it is importance to selected machining parameters such as cutting speed and depth of cut. For this Study, the main effect of machining parameters that will be analyzed is cutting speed, and depth of cut on the mill steel. This study will conduct to see the relationship between parameters milling and surface roughness. The workpiece have been machining using a conventional milling machine Hwacheon HMV-1100 without coolant and the surface finish will be measured using surface roughness tester. In this Study, it was found that lowest value of surface roughness, which is 0.442 um, has been obtained with machining parameters of 750 rpm cutting speed, 0.2 mm depth of cut and feed rate of 0.1 mm/rev. The highest value of surface roughness, which is 2.171 µm, has been obtained with machining parameters of 370 rpm cutting speed, 0.4 mm depth of cut and feed rate of 0.1 mm/rev. In conclusion, The impacts of cutting speed and depth of cut are the variables that influence the workpiece''s mild steel''s surface finish.